Enhanced Seebeck coefficient by energy filtering in Bi-Sb-Te based composites with dispersed Y2O3 nanoparticles. (March 2017) - Madavali, Babu; Kim, Hyo-Seob; Lee, Kap-Ho; Hong, Soon-Jik
Abstract: The incorporation of ceramic nanoparticles in the bulk thermoelectric matrix is one of the new strategies to boost the Seebeck coefficient. In this research, different weight percentages of Y2 O3 (2, 4, and 6) nanoparticles (NPs) were incorporated into the pre-alloyed BiSbTe powder for making nanocomposites (NCs) by mechanical milling. The resultant NCs powders were subsequently consolidation by spark plasma sintering (SPS) at 450 °C. The existence of Y2 O3 nano-inclusions was confirmed by x-ray diffraction and TEM-SAED analysis. The hardness of the nanocomposites was significantly improved (>49%) compared to that of pure BiSbTe, and this was attributed to grain-boundary hardening and to a dispersion strengthening mechanism. The electrical conductivity decreased while the Seebeck coefficient significantly improved (45%) at room temperature for the NCs to which 2 wt% Y2 O3 was added. This was due to the scattering of carriers through the energy filtering effect. The electronic component of the thermal conductivity greatly contributed to the reduction of total thermal conductivity (22%) in BiSbTe NCs to which 6 wt% Y2 O3 was added. A peak ZT of 1.24 was achieved for BiSbTe/(2 wt%) Y2 O3 NCs due to reduction in their thermal conductivity and improved Seebeck coefficient values. Graphical abstract: Significant improvement in Seebeck coefficient via energy filtering effect, and strong reduction in thermal conductivity from carrier/phonon scattering contributed to the enhanced ZT at room temperature. Highlights: P-type BiSbTe/Y2 O3 nanocomposites have been fabricated by ball milling and Spark plasma sintering. Seebeck coefficient is eminently improved (45%) due to scattering of carriers through the energy filtering effect. Thermal conductivity is reduced by 22% in nanocomposites due to carrier/phonon scattering. Hardness of nanocomposites was significantly improved (>49%) compared to pure BiSbTe.